MANAJEMEN PERGURUAN TINGGI ISLAM BERBASIS PESANTREN - Slamet; Mohammad Nurul Huda (el Hakim Press, 2024)
This study aims to determine the implementation of management functions, student management, academic culture development management and alumni management at Islamic religious colleges based on pesantren. The method used in this research is descriptive qualitative. The data in this study were obtained from interviews, observations and documentation with the research subjects, namely the head of STAI Luqman Al-Hakim, the vice chairman of student affairs, the head of caring and alumni. The findings of this study PTAI and Islamic Boarding School are able to integrate to achieve the goal of excellence from the uniqueness of PTAI as an academic entity by giving birth to scholars and boarding schools with its function as a preacher / cleric printer. Management functions are aligned and optimal when the vision and orientation are clear and measurable, namely the birth of cadre scholars. Student management is integrated between the development of academic culture and pesantrenan with the optimization of resources, methods of fostering the character of the quran, pesantren culture, educative rules and means (mosques, dormitories, campuses, pesantren) to give birth to alumni who are ready to carry out the task of developing organizations.